Abstracts of the 12th Congress of the African Association of Nephrology (Accra, Ghana, 20-23 February, 2013) - Assounga, Alain (African Journal of Nephrology, 2013)
<span style="color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Accra, Ghana, 20-23 February, 2013